2015
DOI: 10.4049/jimmunol.1402838
|View full text |Cite
|
Sign up to set email alerts
|

The Levels of the Lectin Pathway Serine Protease MASP-1 and Its Complex Formation with C1 Inhibitor Are Linked to the Severity of Hereditary Angioedema

Abstract: C1 inhibitor (C1-INH) is known to form complexes with the lectin complement pathway serine proteases MASP-1 and MASP-2. Deficiency of C1-INH is associated with hereditary angioedema (HAE), an autosomal inherited disease characterized by swelling attacks caused by elevated levels of bradykinin. MASP-1 was shown to cleave high m.w. kininogen into bradykinin; therefore, we hypothesized that MASP-1 levels and the quantity of MASP-1/C1-INH complexes might be associated with different paraclinical and clinical outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 38 publications
2
22
0
Order By: Relevance
“…One possibility is that fluid-phase activation of lectin pathway proteases occurs slowly at a constant rate, but active MASP-1 and MASP-2 are rapidly inactivated by their natural inhibitors like C1 inhibitor and antithrombin (37). This assumption is supported by the presence of MASP-1-C1-inhibitor and MASP-1-antithrombin complexes in normal serum and plasma (38). Importantly, as active MASP-3 is not inhibited by C1 inhibitor (39) or any other identified serpin, it could slowly accumulate in such a scenario.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that fluid-phase activation of lectin pathway proteases occurs slowly at a constant rate, but active MASP-1 and MASP-2 are rapidly inactivated by their natural inhibitors like C1 inhibitor and antithrombin (37). This assumption is supported by the presence of MASP-1-C1-inhibitor and MASP-1-antithrombin complexes in normal serum and plasma (38). Importantly, as active MASP-3 is not inhibited by C1 inhibitor (39) or any other identified serpin, it could slowly accumulate in such a scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently two independent publications corroborated the role of antithrombin in lectin pathway regulation detecting MASP‐1–antithrombin complexes in the blood of patients having various diseases [e.g. hereditary angioedema (HAE), systemic lupus erythematosus, polytrauma] . The latter publication also demonstrates that blood clotting activates the lectin pathway .…”
Section: Interaction Between the Different Cascade Systems In The Bloodmentioning
confidence: 85%
“…Taken into account the high autoactivation potential of MASP‐1, it is also possible that MASP‐1 contributes to the elevated baseline level of bradykinin observed in the blood of the HAE patients . Indeed, a recent publication reported that that there is a significant amount of circulating MASP‐1‐C1 inhibitor complex in the resting blood of healthy individuals . This means that MASP‐1 is being continuously (auto)activated in the plasma at a slow rate (similarly to the “tick over” of C3), but the active MASP‐1 is present only for a limited period of time, as it is inactivated by C1 inhibitor (and possibly by antithrombin).…”
Section: Interaction Between the Different Cascade Systems In The Bloodmentioning
confidence: 99%
See 1 more Smart Citation
“…MASP-1 has been recently shown to cleave bradykinin from HMWK [17] and its levels, together with the complex MASP1-C1-INH, have been related to disease severity in C1-INH-HAE [18].…”
Section: Lectin Pathway Of the "Complement System"mentioning
confidence: 99%